MiRNAs as Anti-Angiogenic Adjuvant Therapy in Cancer: Synopsis and Potential - Lahooti, Behnaz; Poudel, Sagun; Mikelis, Constantinos M.; Mattheolabakis, George (Frontiers in Oncology, 2021)
Angiogenesis is a key mechanism for tumor growth and metastasis and has been a therapeutic target for anti-cancer treatments. Intensive vascular growth is concomitant with the rapidly proliferating tumor cell population and tumor outgrowth. Current angiogenesis inhibitors targeting either one or a few pro-angiogenic factors or a range of downstream signaling molecules provide clinical benefit, but not without significant side effects. miRNAs are important post-transcriptional regulators of gene expression, and their dysregulation has been associated with tumor progression, metastasis, resistance, and the promotion of tumor-induced angiogenesis. In this mini-review, we provide a brief overview of the current anti-angiogenic approaches, their molecular targets, and side effects, as well as discuss existing literature on the role of miRNAs in angiogenesis. As we highlight specific miRNAs, based on their activity on endothelial or cancer cells, we discuss their potential for anti-angiogenic targeting in cancer as adjuvant therapy and the importance of angiogenesis being evaluated in such combinatorial approaches.